FLASHCARD-BASED ONLINE EDUCATIONAL GAME FOR IMPROVING HIV-AIDS KNOWLEDGE AND STIGMA - Intan Farida Yasmin; Titiek Djannatun; Dian Widiyanti (Universitas Airlangga, 2023)
Introduction: The burden of HIV-AIDS cases in Indonesia remains high, while HIV-AIDS promotion programs targeting students remain low. Game-based learning has not been investigated as an alternative method for improving HIV-AIDS awareness among students. Aims: this study quantifies the impact of the flashcard-based educational game invented by YARSI HIV-AIDS Care on high school students in Jakarta. Method: A simple randomized controlled study was conducted among 112 SMA 27 Jakarta students (intervention, n=56; control, n= 56). The HIV-AIDS knowledge and attitude scores before and after the educational game were evaluated using a validated questionnaire. An intervention using a flashcard-based game is conducted online. Univariate and Bivariate analyses of the pre-and post-scores for both groups were performed. Result: Following the game, there was a considerable improvement in the HIV-AIDS comprehensive knowledge scores (pre-test vs. post-test, 65 vs. 90, p<0.01), while the control score remained unchanged. The intervention group also had higher knowledge and attitude scores than did the control group (p<0.01). Conclusion: Flashcard-based education games significantly increased comprehensive HIV-AIDS knowledge and positive attitudes toward HIV-AIDS. Thus, this method could be implemented in HIV-AIDS promotion programs that target students